2006
DOI: 10.1080/10408690590957250
|View full text |Cite
|
Sign up to set email alerts
|

Creating Proteins with Novel Functionality via the Maillard Reaction: A Review

Abstract: Proteins are widely utilized to add functional properties, such as gelling and emulsification to foods. These attributes depend on a number of factors such as molecular structure of the protein, the pH, and the composition of its chemical environment. There is substantial evidence to suggest that the functional properties of food proteins can be further improved by derivatization. Covalent bonding of proteins to polysaccharides and smaller reducing sugars via the Maillard reaction has been shown to alter the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
313
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(322 citation statements)
references
References 127 publications
(195 reference statements)
2
313
0
7
Order By: Relevance
“…In recent years, the Maillard-type glycation has been widely used to generate new glycoproteins, by conjugating carbohydrates covalently into food proteins (Zhu, Damodaran, & Lucey, 2008). Past studies have shown that the generated glycoproteins had improved functional properties including emulsifying properties (Diftis & Kiosseoglou, 2003) and solubility (Oliver, Melton, & Stanley, 2006). However, the Maillard-type glycation of the proteins might have some adverse effects that cannot be ignored both in practical applicability and safety, such as a difficulty in reaction control, a longer reaction time, the undesired color and flavor of products, and the formation of some potential mutagenic compounds (Brands, Alink, Van-Boekel, & Jongen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Maillard-type glycation has been widely used to generate new glycoproteins, by conjugating carbohydrates covalently into food proteins (Zhu, Damodaran, & Lucey, 2008). Past studies have shown that the generated glycoproteins had improved functional properties including emulsifying properties (Diftis & Kiosseoglou, 2003) and solubility (Oliver, Melton, & Stanley, 2006). However, the Maillard-type glycation of the proteins might have some adverse effects that cannot be ignored both in practical applicability and safety, such as a difficulty in reaction control, a longer reaction time, the undesired color and flavor of products, and the formation of some potential mutagenic compounds (Brands, Alink, Van-Boekel, & Jongen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Caseinate is one of these protein ingredients with good nutritive values and desired functional properties, and thus often used in food processing (Oliver, Melton, & Stanley, 2006). However, chemical modifications of proteins can lead to both structure and property innate and adaptive immunity and their roles in phagocytosis (Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The well-known chemical modifications of proteins include acetylation, succinylation, esterification, amidation, and other reactions, have been used in the past studies, and are not introduced here. In addition, protein glycation has become an area of considerable research interest in recent years (Oliver, Melton, & Stanley, 2006). The well-known Maillard reaction is able to glycate proteins (Martins, Jongen, & Van Boekel, 2000), via the formation of protein-saccharide conjugates.…”
Section: Introductionmentioning
confidence: 99%